2012
DOI: 10.1109/tifs.2012.2187515
|View full text |Cite
|
Sign up to set email alerts
|

Coding With Scrambling, Concatenation, and HARQ for the AWGN Wire-Tap Channel: A Security Gap Analysis

Abstract: This study examines the use of nonsystematic channel codes to obtain secure transmissions over the additive white Gaussian noise (AWGN) wire-tap channel. Unlike the previous approaches, we propose to implement nonsystematic coded transmission by scrambling the information bits, and characterize the bit error rate of scrambled transmissions through theoretical arguments and numerical simulations.We have focused on some examples of Bose-Chaudhuri-Hocquenghem (BCH) and low-density paritycheck (LDPC) codes to esti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 24 publications
1
93
0
Order By: Relevance
“…In particular, scrambling is defined perfect when even a single error at the descrambler input produces about half of the information bits in error at the output and with randomly distributed error positions. In our previous papers [14,15], we have verified that perfect scrambling is rather easy to approach in practice.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In particular, scrambling is defined perfect when even a single error at the descrambler input produces about half of the information bits in error at the output and with randomly distributed error positions. In our previous papers [14,15], we have verified that perfect scrambling is rather easy to approach in practice.…”
Section: Introductionmentioning
confidence: 63%
“…On the other hand, the use of punctured codes brings the disadvantage of an increase in the power consumption. In some of our previous papers [12][13][14], we have demonstrated that similar, and even larger, reductions in the security gap can be achieved by using scrambled transmissions, and with considerable power saving with respect to punctured codes. A similar approach can also be used in the context of IEEE 802.11 wireless networks, where less powerful convolutional codes are used in the place of LDPC codes [15].…”
Section: Introductionmentioning
confidence: 66%
“…Bit error probability of the eavesdropper versus the security gap (for P max main = 10 −5 ) when the convolutional code [657 435] encodes the data bits for 3 different codeword lengths and two different random bit encoders in (26) and (28). Results corresponding to the optimized punctured LDPC codes reported in [8] and [9] are also included for comparison. data bits and a subset of its dual for random bits.…”
Section: B Noisy Main Channelmentioning
confidence: 99%
“…Specifically, punctured LDPC codes are exploited for physical layer security in [7]. Furthermore, [8] demonstrates that using nonsystematic codes obtained from scrambling information bits of a systematic code are quite effective to reduce the security gap, while [9] applies different techniques including scrambling, concatenation, and hybrid automatic repeat-request to LDPC and BCH codes in order to further reduce the security gap.…”
Section: Introductionmentioning
confidence: 99%
“…A suboptimal strategy of power allocation and scheduling to maximize the overall network utility is then derived. The HARQ secrecy scenario is also considered in [9] with a rather different approach, where standard codes are used with the addition of scrambling, but secrecy is expressed in terms of the bit error probability at the eavesdropper. Lastly, the throughput of HARQ without secrecy constraints has been studied in [10], but the analysis does not fit immediately the different scenario where a secret message must be transmitted.…”
Section: Introductionmentioning
confidence: 99%